The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4317/jced.56640
|View full text |Cite
|
Sign up to set email alerts
|

Publication trends in journal of clinical and experimental dentistry

Abstract: Background Journal of Clinical and Experimental Dentistry (J Clin Exp Dent; JCED) is an English language journal published by the Spanish Society of Oral Surgery, and has been online since 2009. It is indexed in PubMed Central and Scopus since 2012, with monthly publications since 2016. The purpose of this article was to review and analyse the publications in this journal since its inception, over a period of 11 years (2009-2019). Material and Methods This paper assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Bibliometric studies have shown that there are differences between dental subjects, study categories, and thematic areas. In the last bibliometric reviews of dentistry journals, some specific areas stand out, such as dental materials (Moraes et al 2020), oral pathology (Bhalla and Chockattu 2020), and endodontics (Estrela Research, Society and Development, v. 10, n. 13, e299101321279, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i13.21279 3 et al 2020) but the area of special patients is not even mentioned. However, in some bibliometric reviews with a specific theme in pediatric dentistry, there was a very low percentage of articles published with a specific theme of patients with special needs (6.5%) (Adobes Martin et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bibliometric studies have shown that there are differences between dental subjects, study categories, and thematic areas. In the last bibliometric reviews of dentistry journals, some specific areas stand out, such as dental materials (Moraes et al 2020), oral pathology (Bhalla and Chockattu 2020), and endodontics (Estrela Research, Society and Development, v. 10, n. 13, e299101321279, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i13.21279 3 et al 2020) but the area of special patients is not even mentioned. However, in some bibliometric reviews with a specific theme in pediatric dentistry, there was a very low percentage of articles published with a specific theme of patients with special needs (6.5%) (Adobes Martin et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric methods have been used in several fields of dentistry (Patil et al 2020;Ahmad et al 2020;Liu et al 2020) and specific dentistry journals (Valderrama et al 2020;Bhalla and Chockattu, 2020). The aim of this study was to assess bibliometric characteristics and the worldwide tendency of all articles on cerebral palsy and oral health.…”
Section: Introductionmentioning
confidence: 99%
“…Perazzo et al (2019) have analyzed the top 100 most-cited papers in pediatric dentistry journals and observed the most cited area was cariology, followed by dental growth and development and behavioral and epidemiological science. Other bibliometric analysis demonstrated a minor contribution of papers including patients with special needs (Bhalla and Chockattu, 2020). These data can explain the low absolute number of publications in the researched topic found in this study.…”
Section: Discussionmentioning
confidence: 45%
“…Various authors performed a bibliometric analysis but received a minor contribution from the fields. (23,24,25). There was a marked growth in the number of publications over the last few years for the evaluation of articles on laser and dental hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%